THE IMPACT OF THE QUALITY OF ACCOUNTING INFORMATION SYSTEMS ON INCREASING TAX REVENUES: AN APPLIED STUDY IN THE IRAQI GENERAL TAX AUTHORITY - Assistant Professor: Ali Faleh Khalaf; Lecturer: Saoussen Boujelben (Scholar Express Journals, 2024)
The research aims to demonstrate the role that the quality of accounting information systems can play in increasing tax revenue collection by improving the suitability and reliability of accounting information. This information becomes an important and essential tool for making administrative decisions that align with the requirements of the contemporary business environment. The research was conducted in the Iraqi General Tax Authority, using data from the fiscal year 2022. The study reached several conclusions, the most significant of which is that our empirical results confirm the significant effect of accounting information systems in enhancing tax revenues. The tax administration should prioritize the utilization of accounting information systems across all departments of the General Tax Authority, as this significantly impacts both the increase in tax revenues and the efficiency of collection methods.
Keywords: Quality of Accounting Information Systems; Tax Revenues; Iraqi General Tax Authority